EFFECT OF SUPEROTEMPORAL CLEAR CORNEAL INCISION ON PRE EXISTING ASTIGMATISM AFTER PHACOEMUSIFICATION SURGERY - Mohammad Aamir Khan,; Faisal, Zainab; Bushra Aaqil,; Zubairullah Khan,; Qazi Maaz Ul Haq,; Muhammad Adnan Rashid, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Historically, patients undergoing cataract surgery were at an increased risk of developing surgically induced astigmatism with the advent of modern methods of cataract surgery, the focus shifted towards smaller sized incisions and minimally invasive surgery. Smaller incision produces less post-operative change in astigmatism and early visual rehabilitation as compared to larger incisions. This study was conducted to evaluate and compare the difference between pre and post op corneal astigmatism among patients undergoing phacoemulsification surgery, for cataract, via a superotemporal clear corneal incision. Methods: This was a longitudinal study that enrolled 85 patients between the ages of 40 and 90 years at Ophthalmology Department, Jinnah International Hospital, Abbottabad. Patients were divided into 2 groups according to their pre exiting astigmatism. Group A, With the Rule (WTR), astigmatism and Group B, Against the Rule (ATR) astigmatism. Astigmatism was measured and compared pre operatively, and on day 1, day 7 and day 30 post operatively via auto kerato-refractometer. Results: The mean astigmatism in patients in Group A (WTR astigmatism) preoperatively was 0.76 Diopters, whereas patients in Group B (ATR astigmatism) had a mean pre operative astigmatism of 0.68 Diopters. Mean astigmatism post operatively at day 30 was 0.86 Diopters for Group A, and 1.02 Diopters for Group B. Only 2 out of 36 patients in Group A had a shift to ATR astigmatism, whereas 4 out of 49 patients in Group B had a shift to WTR astigmatism by post op day 30. Conclusion: Superotemporal clear corneal incision is a relatively stable and effective site for incision during phacoemulsification surgery, and causes negligible change in pre operative astigmatism.